Septal cholinergic input to CA2 hippocampal region controls social novelty discrimination via nicotinic receptor-mediated disinhibition - Pimpinella, Domenico; Mastrorilli, Valentina; Giorgi, Corinna; Coemans, Silke; Lecca, Salvatore; Lalive, Arnaud L; Ostermann, Hannah; Fuchs, Elke C.; Monyer, Hannah; Mele, Andrea; Cherubini, Enrico; Griguoli, Marilena (eLife, 2021)
Acetylcholine (ACh), released in the hippocampus from fibers originating in the medial septum/diagonal band of Broca (MSDB) complex, is crucial for learning and memory. The CA2 region of the hippocampus has received increasing attention in the context of social memory. However, the contribution of ACh to this process remains unclear. Here, we show that in mice, ACh controls social memory. Specifically, MSDB cholinergic neurons inhibition impairs social novelty discrimination, meaning the propensity of a mouse to interact with a novel rather than a familiar conspecific. This effect is mimicked by a selective antagonist of nicotinic AChRs delivered in CA2. Ex vivo recordings from hippocampal slices provide insight into the underlying mechanism, as activation of nAChRs by nicotine increases the excitatory drive to CA2 principal cells via disinhibition. In line with this observation, optogenetic activation of cholinergic neurons in MSDB increases the firing of CA2 principal cells in vivo. These results point to nAChRs as essential players in social novelty discrimination by controlling inhibition in the CA2 region.
Gesehen am 08.02.2022